Measuring Initiative, Empathy, and Resilience among High School Students - Kamariah Latief; Dasim Budimansyah; Ace Suryadi; Encep Syarief Nurdin; Yadi Ruyadi; Asep Dahliyana (Universitas Pendidikan Ganesha, 2025)
The low level of student initiative, despite relatively high levels of empathy and resilience, presents a significant challenge in character development at the secondary level, as it has the potential to hinder independence, proactive behavior, and readiness to meet both academic and life demands. This study aims to analyze the relationship between initiative, empathy, and resilience, while also identifying their implications for strategies to strengthen student character. Employing a quantitative descriptive correlational design, the research involved 300 respondents using an 18-item questionnaire that was both valid and reliable (Cronbach’s α = 0.86–0.90). Data were collected through surveys and analyzed using descriptive statistics and Pearson’s correlation test. The findings indicate that empathy ranked highest, followed by resilience, while initiative ranked lowest, highlighting the need for interventions to foster autonomy and proactive behavior. A strong positive correlation was found among the three variables, particularly between initiative and resilience (r = 0.79), indicating interdependence. These results recommend enhancing empathy through Social and Emotional Learning (SEL), resilience through counseling, and initiative through independent projects and coaching, in alignment with the Pancasila Student Profile (Profil Pelajar Pancasila) and the World Economic Forum’s character taxonomy, to support students’ holistic development.